Asuhan Keperawatan pada Anak dengan Masalah Ansietaspre-Operasi dengan Terapi Non Farmakologi Distraksi Visual di Ruangan Catelia RSUD Undata Provinsi Sulawesi Tengah: Nursing Care in Children with Preoperative Anxiety Problems with Non Pharmacological Therapy pf Visual Distraction in The Room of Catelia Undata Hospital Central Sulawesi Province - Pelek, Aisi; Iriani, Indri; Rabiah (Jurnal Kolaboratif Sains, 2024)
Pre-operative anxiety is the anxiety experienced by patients before undergoing surgery. Handling this anxiety is important because it can affect the success of the operation and the patient's recovery. The research method used is descriptive research with a direct observation approach and interviews by describing or describing care problems for clients who experience preoperative anxiety, which is carried out through a care approach that includes assessment, diagnosis, intervention, implementation and evaluation of care. The aim of using visual distraction therapy is to divert children's attention from their anxiety and fear of surgical procedures, so that they feel calmer and more comfortable before entering the operating room. The research results obtained after the visual distraction treatment intervention of watching videos were An. A said he was not afraid and was ready for surgery, An. A looks calm, An. Looks relaxed and concentration improves. The conclusion of this research is that visual distraction therapy by watching videos is effective in diverting pre-operative anxiety in client An. A.